UTERUS PRESERVING TREATMENT MODALITIES FOR ABNORMAL INVASIVE PLACENTA: A SYSTEMATIC REVIEW - Aromatika, Legina; Nofriyadi, Teddy; Juliana, Mutia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: When a focal accreta is identified, conservative intervention may be considered, such as preserving the uterus and placenta and then enduring methotrexate therapy or pelvic artery embolisation. In spite of this, surgical treatment remains the gold standard for the condition. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 401 articles, whereas the results of our search on SagePub brought up 289 articles. The results of the search conducted for the last year of 2013 yielded a total 43 articles for PubMed and 31 articles for SagePub. In the end, we compiled a total of 20 papers, 12 of which came from PubMed and 8 of which came from SagePub. We included seven research that met the criteria. Conclusion: Due to the intricacy of surgery, conservative management should be reserved for individuals who are interested in preserving their fertility as well as those who have major disease.